2022
DOI: 10.1155/2022/9180000
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Process Optimization for Development of Guar Gum‐Based Biodegradable Hydrogel Film Using Response Surface Methodology

Abstract: In the current study, a guar-gum-based biodegradable hydrogel film was prepared using an initiator (potassium persulfate), crosslinker (N-N methyl bis acrylamide), and plasticizer (glycerol) for packaging of fruits and vegetables. The effect of independent variables (initiator, crosslinker, and plasticizer) on the biodegradation (% wt. loss), color difference (ΔE), hardness (N), swelling index (%), and transparency (%) of the film was studied using Box–Behnken design, random surface methodology (RSM). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%